A Study of the Impact of Motivation and Job Satisfaction on the Private School Teachers Performance and Commitment (International Journal of Innovative Research in Engineering & Management, 2022)
Psychology has, essentially, benefited  people because it can explain why people behave the way  they do. A psychologist with this level of professional  insight can help people improve their decision-making,  stress management, and behavior by understanding past  behavior to better predict future behavior. All of this can  lead to a more successful career, better relationships,  increased self-confidence, and overall improved  communication. Psychology's scope was once limited to  people's mental health. Psychology is used to help mentally  stressed people who had been through traumatic  experiences. Present research is based upon a survey for  the impact of motivation and job satisfaction upon the  organization commitment and performance of teachers in  private school.
Keywords: Job Satisfaction; Employees’ Performance; Motivation; Organizational Commitment